Making reasonable decisions: a qualitative study of medical decision making in the care of patients with a clinically significant haemoglobin disorder. Issue 5 (9th June 2015) - Crowther, Helen J.; Kerridge, Ian
Abstract Rationale, aims and objectives Therapies utilized in patients with clinically significant haemoglobin disorders appear to vary between clinicians and units. This study aimed to investigate the processes of evidence implementation and medical decision making in the care of such patients in NSW, Australia. Methods Using semi‐structured interviews, 11 haematologists discussed their medical decision‐making processes with particular attention paid to the use of published evidence. Transcripts were thematically analysed by a single investigator on a line‐by‐line basis. Results Decision making surrounding the care of patients with significant haemoglobin disorders varied and was deeply contextual. Three main determinants of clinical decision making were identified – factors relating to the patient and to their illness, factors specific to the clinician and the institution in which they were practising and factors related to the notion of evidence and to utility and role of evidence‐based medicine in clinical practice. Conclusions Clinicians pay considerable attention to medical decision making and evidence incorporation and attempt to tailor these to particular patient contexts. However, the patient context is often inferred and when discordant with the clinician's own contexture can lead to discomfort with decision recommendations. Clinicians strive to improve comfort through the use of experience and trustworthy evidence.